Group Counseling Using Symbolic Modeling Techniques Containing the Panji Story to Increase the Adversity Quotient of Students Council - Adyana Ajeng Ratuwulan; Titin Indah Pratiwi; Bambang Dibyo Wiyono (PSDKU Guidance and Counseling, Universitas Negeri Surabaya, 2026)
Adversity quotient is an individual's ability to overcome obstacles and maintain effort when faced with difficult situations. This ability is important for OSIS (Student Council) administrators who face various demands in implementing organizational work programs. However, initial observations suggest a tendency towards low fighting spirit and difficulties for some OSIS administrators in addressing organizational challenges. This study aims to determine the effectiveness of symbolic modeling techniques based on the values ​​of the Panji Story in group counseling to increase the adversity quotient of OSIS administrators. The study used a single-subject research design with four OSIS administrators of SMKN 1 Plosoklaten who had low adversity quotient levels based on the initial assessment results. Interventions were provided through group counseling services using symbolic modeling techniques with the Panji Story as a medium for modeling adaptive behavior in facing difficulties. Data analysis was conducted by comparing baseline and intervention conditions. The results showed that the application of symbolic modeling techniques based on the Panji Story in group counseling was able to increase the adversity quotient of the research subjects. These findings suggest that the integration of local wisdom in guidance and counseling services can be an alternative approach to developing students' psychological resilience.